2021
DOI: 10.57111/econ.20(4).2021.24-30
|View full text |Cite
|
Sign up to set email alerts
|

The shadow economy as a threat to the economic security of the state

Svitlana Onyshchenko,
Alina Hlushko,
Oleksandr Kivshyk
et al.

Abstract: The relevance of scientific research is determined by the need to substantiate the specifics of the impact of the shadow economy as a polysystemic phenomenon, inherent in any national economic system, on the economic security of the state. The purpose of the work was to study the size, trends of the shadow economy in Ukraine and its impact on the economic security of the state in order to form the directions of unshadowing the economy as a necessary condition for the accelerated economic growth of Ukraine. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Current issues related to labour undeclared work (factors, spheres, socio-economic consequences of its spread, mechanisms and priorities for regulation, mitigation, prevention) are addressed in works devoted to: Problems of adequate remuneration of labour and functioning of wage systems (State Labour Service of Ukraine, 2021;Onyschenko, 2020;EU -ILO, 2018;National Institute of Strategic Studies, 2011); processes of shadow economy, features of functioning of its shadow segments (EU -ILO, 2018;Tsvihun, Nechyporuk, 2018;Shevchuk, 2016;Savchenko, Iordanov, 2012;National Institute of Strategic Studies, 2011); non-standard labour relations, temporary (loan) workers (State Labour Service of Ukraine, 2024; EU - ILO, 2018;Lahutina, 2015;Kurzina, 2012). In terms of employment status, the majority of undeclared workers in 2017 reported that they were unemployed (33.5%), employed (31.2%), selfemployed (18.4%), retired (10.5%) and studying (1.9%) (EU -ILO, 2018).…”
Section: Methodological Principles For Identifying Undeclared Labourmentioning
confidence: 99%
See 1 more Smart Citation
“…Current issues related to labour undeclared work (factors, spheres, socio-economic consequences of its spread, mechanisms and priorities for regulation, mitigation, prevention) are addressed in works devoted to: Problems of adequate remuneration of labour and functioning of wage systems (State Labour Service of Ukraine, 2021;Onyschenko, 2020;EU -ILO, 2018;National Institute of Strategic Studies, 2011); processes of shadow economy, features of functioning of its shadow segments (EU -ILO, 2018;Tsvihun, Nechyporuk, 2018;Shevchuk, 2016;Savchenko, Iordanov, 2012;National Institute of Strategic Studies, 2011); non-standard labour relations, temporary (loan) workers (State Labour Service of Ukraine, 2024; EU - ILO, 2018;Lahutina, 2015;Kurzina, 2012). In terms of employment status, the majority of undeclared workers in 2017 reported that they were unemployed (33.5%), employed (31.2%), selfemployed (18.4%), retired (10.5%) and studying (1.9%) (EU -ILO, 2018).…”
Section: Methodological Principles For Identifying Undeclared Labourmentioning
confidence: 99%
“…5 No. 1, 2024 In addition to systemic measures to increase the level of wages in Ukraine, domestic and foreign experts often include in the urgent list of nondeclaration of work that prevents such priorities as (EU -ILO, 2018;Tsvihun, Nechyporuk, 2018;Shevchuk, 2016;Savchenko, Iordanov, 2012): -Improving the tax system in the following areas: coordinated optimisation of tax administration mechanisms and the legislative framework that defines the conditions for business development and expansion at the initial stage, including the establishment of tax holidays on income tax for companies that increase their payroll and improve working conditions for full-time employees; balancing the tax burden of economic entities according to the groups of their production capacities, as well as according to the level of their involvement in programmes of modernisation and diversification of the national economy; maintaining the balance between the fiscal and regulatory functions of taxes, including increasing the transparency of the system of tax benefits; reduction of the fiscal burden on the wage fund; effective monitoring of offshore zones; justified use of amnesty mechanisms in relation to shadow capital of non-criminal origin, while opening ways for its legal investment, encouraging the investment use of legalised funds in the internal interests of the national economy; -monitoring the informal economy and the illegal labour market, in particular in terms of tracking the practice of paying wages "in an envelope"; strengthening systemic mechanisms to prevent it; -ensuring transparency of the real and service sectors of the economy; state support for innovation and investment projects in the real sector, as well as in other industries whose development contributes to the diversification, modernisation and competitiveness of the Ukrainian economy; -coordination of a set of mechanisms for identifying and bringing to legal liability business entities that are dishonest in the use of undeclared labour and tax payments; toughening penalties for corruption in the system of issuing permits and licences, as well as for raiding; -prevention of mutual settlements based on barter between business entities; monitoring of formal grounds and processes for the use of borrowed labour; -improvement of the mechanisms of compulsory social insurance in terms of collecting the unified social tax, distribution and use of these funds for their intended purpose.…”
mentioning
confidence: 99%